The comparison of effects of fentanyl and dexmedetomidine as adjuvants to ropivacaine for ultrasound-guided transversus abdominis plane block for postoperative pain in cesarean section under spinal anesthesia -A randomized controlled trial - Bincy Joseph; Sunitha K Zachariah; Saramma P Abraham (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Transversus abdominis plane (TAP) block has been effectively used for anterior abdominal wall analgesia. The aim of the study was to compare the duration of analgesia produced by two drugs fentanyl and dexmedetomidine as adjuvants to ropivacaine in TAP block under ultrasound-guidance after lower segment cesarean section in a randomized controlled trial. Methods: Sixty-four women of American Society of Anaesthesiologists (ASA) physical status II coming for cesarean sections were randomized to receive TAP blocks on each side of the abdomen using the local anesthetic drug 20 ml of 0.5% ropivacaine with either fentanyl 25 mcg or dexmedetomidine 25 mcg. A ten point numerical pain score was done at baseline, at 1 h and then at intervals of 4 h postoperatively. The hemodynamic parameters such as heart rate, blood pressure, and pulse oximetry were also monitored as above. The time to first analgesia demand from the time of the block and the total analgesic consumption were recorded. The statistical analysis was done by Mann-Whitney U test and the analgesics consumption by using Chi-square test with R software. Results: Our primary end-point was to assess the duration of analgesia produced by fentanyl added to ropivacaine for ultrasound-guided TAP block, which were 125 min with Q1-Q3 as 110-180 and dexmedetomidine 130 min with Q1-Q3 as 105-161 (P value = 0.47). The amount of analgesics used in the postoperative period in both the groups were analyzed using the Chi-square test not found to have any significant difference between both the groups (P-value = 0.512). Conclusion: Fentanyl and dexmedetomidine as adjuvants to ropivacaine in ultrasound-guided TAP block were equally effective in both prolongation of analgesia and reducing the total consumption of analgesics.